PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) PERIODE 2019-2023 - Istiqomah Istiqomah; Elyanti Rosmanidar; Khairiyani Khairiyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research is motivated by the Current Ratio and Debt to Asset Ratio which causes Return On Assets to fluctuate. The objektives of this research are (1) To determine whether or not there is an influence of the Current Ratio and Debt to Asset Ratio on Return On Assets simultaneously. (2) To determine whether or not there is a partial influence of the Current Ratio and Debt to Asset Ratio on Return On Assets. The sample used in this research was 19 Food and Beverage companies listed in the Indonesian Sharia Stock Index (ISSI) out of 34 tahen using the purposive sampling method in 2019-2023. This research uses quantitative methods and a descriptive approach, by collecting documentary data where data is obtained from company documents via www.idx.co.id and then carrying out various tests such as descriptive statistical analysis tests, panel data regression analysis tests, simultaneous tests (F), partial test (t), coefficient of determination test using the Eviews 9 application tool.The research results show that (1) the Current Ratio and Debt to Asset Ratio semultaneously have no effect on Return On Assets in Food and Beverage companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2019-2023 period. (2) Current Ratio and Debt to Asset Ratio partially have no effect on Return On Assets in Food and Beverage companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2019-2023 period.